2014
DOI: 10.1016/j.physc.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Vortex–antivortex annihilation in mesoscopic superconductors with a central pinning center

Abstract: In this work we solved the time-dependent Ginzburg-Landau equations, TDGL, to simulate two superconducting systems with different lateral sizes and with an antidot inserted in the center. Then, by cycling the external magnetic field, the creation and annihilation dynamics of a vortex-antivortex pair was studied as well as the range of temperatures for which such processes could occur. We verified that in the annihilation process both vortex and antivortex acquire an elongated format while an accelerated motion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In figure 4 One can notice that in both systems a quasi phase slip line is formed [57]. Such region appears due to the attraction between the vortex and the antivortex which causes an elongation of their cores [21]. After the annihilation, such line disappears.…”
Section: Constant Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In figure 4 One can notice that in both systems a quasi phase slip line is formed [57]. Such region appears due to the attraction between the vortex and the antivortex which causes an elongation of their cores [21]. After the annihilation, such line disappears.…”
Section: Constant Temperaturementioning
confidence: 99%
“…Recently, Zadorosny et al [21] studied similar systems and have shown that the V-AV pair acquires an elongated shape which creates a channel between the border of the system and the hole. In the analysis of the V-AV pair motion it was also shown that such specimens acquire an acceleration in the early and final stages of the annihilation process, with a nearly constant velocity motion between these stages.…”
Section: Introductionmentioning
confidence: 99%
“…The manipulation of single, multi, and giant vortex states in mesoscopic superconductors are very important for applications of spins, fluxtronic, medicine, etc [2,3,4,5,6,7]. It is possible that a vortex anti vortex pairs becomes stable, this stability correspond to the symmetry of the system with pinning centers [8,9], magnetic dots [10,11], arrays of small current loops, hot spot. As is well know, in this kind of process the heat is always present, the heat is diffused and depend on the velocity of such diffusion [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Given this, metastable characteristics of different types of compounds have been studied, for example Mo/MoO_(3-x) for their applications in different types of technologies and magnetoresistance behavior in different types of materials for temperatures close to the critical temperature T_c and more importantly, the study and analogy of the conservation of the spin load in the superconducting state, ie where the spin flows without losses in the superconducting state, behavior that It can be used in systems that emulate the logic gates or spitronic which is one of the branches called to replace the current electronic. Thus, the study of the behavior of the state of vortices in the presence of external current and the dynamics of the vortices given this inclusion of current and the study of depreciation of the superconducting state, due to the presence of an external magnetic field gives an account of possible effects on the state of vortices, which are extremely important in terms of the manipulation of vortices in mesoscopic samples [9][10][11][12][13][14][15][16]. Given this, in this paper we present the behavior of the vortices in a superconducting nano/prism with the inclusion of depreciation of the superconducting state in a given section (deformed system in the Ginzburg-Landau theory), which in our system, establishes the addition of metal contacts, where the inclusion of the current in the system would be carried out, we will study the effect on the magnetization, vortex state and susceptibility, of the external current and temperature of the defects.…”
Section: Introductionmentioning
confidence: 99%